Study of The Auto Transmission Dynamics System and The Effects of Clutch Pressure on Planetary Gear to Optimized the Output Speed - Khai Chu Thanh (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The performance of an automatic transmission is dependent on the dynamics of its components, such as the clutch, planetary gear, and torque converter. In particular, the clutch pressure and planetary gear output speed can affect the overall performance of an automatic transmission. In this paper, It will present the kinematic relations, the dynamics of planetary structure, calculating the impact of braking torque of brake and clutch to slip to the speed of the vehicle Toyota Camry used automatic transmission A140L. Since then, the graph describing the dependence of the transmission ratio gearbox in the hands of, the speed of vehicles on the oil pressure brake and clutch. Finally, modeling and simulation control of such operations by SolidWorks and Matlab Simulink Simmechanics software to clear about this effect